Interperconal Communication On Employe Commitment With Work Engagement As A Mediation Variabel - Aldi Riadi; Yuki Fitria (Human Resource Management Studies, 2022)
This study aims to determine the effect of interpersonal communication on employee commitment by using job engagement as a mediating variable. The research was conducted at PT PLN (Persero) Ulp Air Molek. The population in this study were employees of PT PLN (Persero) Ulp Air Molek. The sample used is 49 employees. Data collection is done through questionnaires and data processing is done by smart pls3. Research shows that there is a positive and significant effect between interpersonal communication and employee engagement at pt pln (persero) ulp air Molek. Interpersonal interaction has a positive and significant effect on job engagement at pt. pln (persero) ulp air Molek, interpersonal communication has a positive and significant effect on work engagement at pt. pln (persero) ulp air Molek, work engagement has no positive and significant effect on employee commitment at pt. pln (persero) ulp air Molek, work involvement does not moderate the influence of interpersonal communication on employee commitment at pt. pln (persero) ulp air molek.